ENERGY DIVERSIFICATION PROJECTS OF THE EUROPEAN UNION IN THE OUTLINING OF THE ENERGY SECURITY POLICY OF UKRAINE - Максак, Г.А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The issues of energy security policy of Ukraine are highlighted in the context of search for regional collective forms of energy cooperation, which are based on common democratic principles. The attention is stressed on the energy policy of the European Union as forming factor for energy security policy of Ukraine.